Mullite whisker toughened mullite coating to enhance the thermal shock resistance of SiC pre-coated carbon/carbon composites. Issue 18 (15th December 2017) - Cao, Liyun; Liu, Jintao; Huang, Jianfeng; Zhou, Lei; Yong, Xiang; Shen, Xuetao; Kong, Luo; Yao, Chunyan
Abstract: In order to improve the thermal shock resistance of the coated carbon/carbon (C/C) composites, a mullite whisker toughened mullite coating was fabricated on the surface of SiC pre-coated C/C composites (SiC-C/C) by molten-salt method with a later hot dipping process. The phase compositions, surface and cross-section microstructures, high temperature thermal shock resistance of the as-prepared multi-layer coatings were investigated. Results show that the introduction of mullite whiskers can effectively improve the density of the mullite outer coating and decrease the cracking of the coating during the thermal shock cycle process. After 100 times thermal shock cycles between 1773 K and room temperature, only 1.87 × 10 −3  g cm −2 weight loss has been detected, indicating the achievement of the excellent thermal shock resistance.